Partial and Total Descemet’s Detachments in a Patient with Severe Terrien’s Marginal Degeneration and Juvenile Idiopathic Arthritis - Amir Hossein Vejdani; Hamid Khakshoor; Michael V. McCaughey; Majid Moshirfar (Case Reports in Ophthalmological Medicine)
A 16-year-old female with juvenile idiopathic arthritis presented with a one-month history of decreasing vision and increasing corneal edema in her left eye. Slit-lamp examination, keratometric measurements, and OCT evaluation led to a diagnosis of Terrien’s marginal degeneration in both eyes along with a complete detachment of Descemet’s membrane in the left eye and partial detachment in the right eye. She was treated with an intracameral injection of air and then topical betamethasone and chloramphenicol which lead to the resolution of symptoms. We further examine the pathophysiology of this disease based on current literature.